Small functionalized iron oxide nanoparticles for dual brain magnetic resonance imaging and fluorescence imaging. Issue 21 (6th April 2021) - Wei, Ruixue; Liu, Yang; Gao, Jinhao; Yong, V. Wee; Xue, Mengzhou
Abstract : SIONs is modified with brain targeting ligands and photosensitizers, and is used for in vivo MR/FL dual-mode high-sensitivity brain imaging. Abstract : The diagnosis of brain diseases is the first key step in effective treatment. In vivo imaging tracers that effectively cross the blood–brain barrier (BBB) and reach areas of brain dysregulation is one focus of accurate diagnosis. Here, our main objective was to develop an iron-based nanoparticle for dual brain magnetic resonance imaging (MRI) and fluorescence imaging studies. Small sized iron oxide nanoparticles (SIONs) were prepared by a solvothermal method. Angiopep-2 was covalently connected to the surface of SIONs to enhance penetration of the BBB. The photosensitizer (chlorin e6, Ce6) was modified on the surface of SIONs to enhance fluorescence imaging to corroborate MRI results. We found that the resultant SIONs@ANG/Ce6/PEG displayed good biocompatibility and excellent MRI and fluorescence detection. Moreover, dual-modal MR/fluorescence imaging demonstrated that SIONs@ANG/Ce6/PEG had high sensitivity and accuracy in imaging of mouse with brain tumors. This work provides a strategy to design dual-modal contrast agents for diagnosis of brain disease.